Rac1 and Akt Exhibit Distinct Roles in Mediating A?-Induced Memory Damage and Learning Impairment. - Cheng, K.C.; Chen, Y.H.; Wu, C.L.; Lee, W.P.; Cheung, C.H.A.; Chiang, H.C. (Molecular Neurobiology, 2021)
Accumulated beta-amyloid (A?) in the brain is the hallmark of Alzheimer's disease (AD). Despite A? accumulation is known to trigger cellular dysfunctions and learning and memory damage, the detailed molecular mechanism remains elusive. Recent studies have shown that the onset of memory impairment and learning damage in the AD animal is different, suggesting that the underlying mechanism of the development of memory impairment and learning damage may not be the same. In the current study, with the use of A?42 transgenic flies as models, we found that A? induces memory damage and learning impairment via differential molecular signaling pathways. In early stage, A? activates both Ras and PI3K to regulate Rac1 activity, which affects mostly on memory performance. In later stage, PI3K-Akt is strongly activated by A?, which leads to learning damage. Moreover, reduced Akt, but not Rac1, activity promotes cell viability in the A?42 transgenic flies, indicating that Akt and Rac1 exhibit differential roles in A? regulating toxicity. Taken together, different molecular and cellular mechanisms are involved in A?-induced learning damage and memory decline; thus, caution should be taken during the development of therapeutic intervention in the future.